The effect of lecithin on liver function of white rats (Rattus norvegicus) induced carbon tetrachloride - Lestari Dewi (Biomedical Engineering, 2016)
Objective: To prove that the lecithin is administered orally has hepatoprotective effect on white male rats given CCl4 intraperitoneally.Material and Methods: 45 male Wistar rats, aged 12 weeks were randomly divided into five groups. Group I, given solvent CMC - Na 0.25% dose of 0.01 ml/g bw, and were given olive oil dose of 1 ml/kg bw, intraperitoneal injection. Group II, given solvent CMC - Na 0.25% dose of 0.01 ml/g bw, and given CCl4 dose of 1 ml/kg bw,dissolved in olive oil by intraperitoneal injection. Group III, IV and V respectively given dose lecithin 90/180/360 mg/ kg bw,dissolved with 0.25% CMC-Na, and  given CCl4 dose of 1 ml/kg bw dissolved in olive oil at a ratio of 1: 1, by intraperitoneal injection. On day 10, 24 hours after administration of CCl4 and olive oil , all the rats dissected, after first anesthetized with ether by inhalation. Then the blood taken from the heart to examine the level of AST and ALT in serum and hepar were taken for  histopathological examination.Results: Giving  lecithin 90/180/360 mg/kg bw were accompanied CCl4 1 ml / kg body weight (group III, IV, and V), shown to reduce levels of SGOT in serum compared with the group that received only CCl4 and giving lecithin 90/180/360 mg/ kg bw with CCl4 1 ml/kg bw  (group III, IV, and V) is proven to reduce ALT levels compared with the group that received only CCl4. On histopathological examination of liver cells proves that lecithin dose 90 / 180/360 mg/kg bw with CCl4 1 ml/kg bw is proven to reduce the amount of cell necrosis than the group that only received CCl4.Conclusion: Lecithin has a protective effect against the liver function.